Oral processing of low water content foods: a development to Hutchings and Lillford’s breakdown path - Hawthornethwaite, David; Ramjan, Yaneez; Rosenthal, Andrew J. (Wiley, 2015)
The “hard to swallow” phenomenon previously reported for peanut paste has been investigated for other oil seed butters. The Temporal Dominance of Sensations (TDS) technique showed similar findings, adding to the list of materials which do not follow Hutchings and Lillford’s break down path (Journal of Texture Studies 19: 103-115). From our data we propose a modification to the Hutchings and Lillford model which allows for initial hydration of dry foods. The model holds well for oil seed pastes and may also help to explain the behaviour of some dry, carbohydrate rich, foods previously constrained to fit extant models.